Dampak Fear Of Missing Out (FOMO) Terhadap Perilaku Ibadah Pada Remaja Di SMA N 8 Muko-Muko - Nurizki, Adin Dela; Amin, Syukri; Syubli, Syubli (Lembaga Riset dan Inovasi Almatani, 2025)
The increasing intensity of social media users resulting in the emergence of anxiety and fear of being left behind and the decline in religious intensity among adolescents is a concerning situation. This study aims to determine how the influence of Fear of Missing Out on adolescent worship behavior. This study was conducted at Sma N 8 Muko-Muko. The sampling method used a purposive sampling technique. The analysis method in this study used simple linear regression analysis. The results of this study indicate that fear of missing out has a negative effect on worship behavior. Fear of missing out (FOMO) can affect adolescent worship behavior through several mechanisms, namely reducing worship time due to fear of missing social activities or trends on social media, changing worship motivation from intrinsic to extrinsic to show religiosity on social media, and reducing the quality of worship due to impaired concentration.